2022
DOI: 10.3390/en15249515
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability of Waste Circulation Models for Sugarcane Biorefinery System in Thailand

Abstract: Sugarcane leaves and trash burning during harvesting, and vinasse management, are major challenges of the Thai sugarcane industry. Identification of the appropriate valorization pathways for both the biomass waste streams using the sugarcane biorefinery concept is necessary. This study aims to assess the environmental sustainability of five CE models, including (1) sugarcane trash for electricity, (2) sugarcane trash to biochar, (3) sugarcane trash as a soil conditioner, (4) vinasse as a bio-fertilizer, and (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…B is the percentage of burnt sugarcane per total sugarcane production (%), and P is the total sugarcane production in 2022/2023 [37] The BL (7.9 t/ha) and CC (64%) were chosen from the study conducted by Sornpoon et al (2014), who observed the actual burning in 13 sugarcane plantations to determine the BL and CC values [35] (Table 3). All EFs used in this study were from the suggested EFs in the previous studies [36,38]. Assuming that only 50% of the burnt SCL in 2022/2023 was utilized for TSAD, the most prevalent pollutants, CO 2 (2.6 Mt), CO (90.1 kt), PM 10 (12.7 kt), and PM 2.5 (9.3 kt), were, respectively emitted with about 2.88 Mt-CO 2 eq emission from SCL open-field burning (Table 4).…”
Section: Estimation Of Reduction In Ghg and Pollutant Emissionsmentioning
confidence: 99%
“…B is the percentage of burnt sugarcane per total sugarcane production (%), and P is the total sugarcane production in 2022/2023 [37] The BL (7.9 t/ha) and CC (64%) were chosen from the study conducted by Sornpoon et al (2014), who observed the actual burning in 13 sugarcane plantations to determine the BL and CC values [35] (Table 3). All EFs used in this study were from the suggested EFs in the previous studies [36,38]. Assuming that only 50% of the burnt SCL in 2022/2023 was utilized for TSAD, the most prevalent pollutants, CO 2 (2.6 Mt), CO (90.1 kt), PM 10 (12.7 kt), and PM 2.5 (9.3 kt), were, respectively emitted with about 2.88 Mt-CO 2 eq emission from SCL open-field burning (Table 4).…”
Section: Estimation Of Reduction In Ghg and Pollutant Emissionsmentioning
confidence: 99%
“…Sugarcane leaves were also employed for electricity generation. Silalertruksa et al [11] introduced the bio-circular-green economy (BCG) for sugarcane to maximize waste usage after harvest. The study assessed the environmental sustainability of five models: sugarcane leaves for electricity generation, biochar, and soil conditioner, and vinasse for bio-fertilizer and electricity generation, with sugarcane leaves used for electricity generation exhibiting the least environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts include soil salinity [13,14], disturbance in soil pH [15], groundwater contamination [16], the accumulation of heavy metals in soils [17], the inhibition of growth in terrestrial plants and aquatic organisms [18], alterations in soil microorganisms [19], and problems associated with regulatory compliance. In Thailand, the recent life cycle assessment shows that using these by-products as soil conditioners and biofertilizers could significantly reduce environmental impacts [20]. Nonetheless, the study on the current practices, farmer perception, and barriers to achieving the BCG goal has not yet been implemented.…”
Section: Introductionmentioning
confidence: 99%